LSPR‐Induced Catalytic Enhancement Using Bimetallic Copper Fabrics Prepared by Galvanic Replacement Reactions. Issue 16 (5th June 2019) - Anderson, Samuel R.; O'Mullane, Anthony P.; Della Gaspera, Enrico; Ramanathan, Rajesh; Bansal, Vipul
Abstract: A simple galvanic replacement (GR) reaction‐based strategy to create copper‐based bimetallic fabrics for photoreductive catalysis is reported. It is shown that a nanostructured Cu@Fabric can be easily converted into bimetallic Cu‐Au@Fabric and Cu‐Ag@Fabric through a spontaneous electroless process that involves simple exposure of copper fabrics to the aqueous solutions of gold and silver ions. The nanoscale hierarchical ordering of cotton fabrics combined with their high porosity and wettability make them outstanding supports for catalyst recovery and reusability. The deposition of miniscule quantities of expensive noble metals on readily available Cu not only reduces the overall catalyst cost, but also plays a major role in improving the catalyst stability and reusability over several cycles through minimizing Cu oxidation. The synergistic effects of the localized surface plasmon resonance (LSPR) properties of Cu, Au, and Ag allow these bimetallic fabrics into highly active visible light photocatalysts. Mechanistic investigation of the photocatalytic activity provides in‐depth information on the electron transfer processes occurring at the catalyst/ reactant interface, revealing electron transport as the rate‐limiting step, which could be overcome under visible light photoillumination conditions. The outcomes enhance the understanding of template‐supported bimetallic nanostructures for LSPR‐induced photocatalysis applications, offering new potential to design multifunctional fabrics for various applications. Abstract : Optically tunable nanostructured cotton fabrics offer versatile potential. Herein, the optical properties of Cu fabrics are controlled by their spontaneous reaction with metal ions to form Cu‐Au and Cu‐Ag fabrics. These surface plasmon resonance–active bimetallic fabrics of controllable compositions offer tunable photoabsorption. This influences the electron transfer processes at the solid/solution interface, making nanostructured bimetallic fabrics outstanding photoredox catalysts.